Constructing the Immune Signature of Schizophrenia for Clinical Use and Research; An Integrative Review Translating Descriptives Into Diagnostics - Kroken, Rune A.; Sommer, Iris E.; Steen, Vidar M.; Dieset, Ingrid; Johnsen, Erik (Frontiers in Psychiatry, 2019)
Schizophrenia is considered as a syndrome comprised by several disease phenotypes, covering a range of underlying pathologies. One of these disease mechanisms seems to involve immune dysregulation and neuroinflammation. While the current dopamine receptor-blocking antipsychotic drugs decrease psychotic symptoms and prevent relapse in the majority of patients with schizophrenia, there is a huge need to explore new treatment options that target other parts of the pathophysiological processes. Such studies should include identification of robust biomarkers to diagnose and monitor the immune biophenotype in schizophrenia, to better select participants for clinical trials with anti-inflammatory and immune-modulating drugs. In this focused review, we describe available methods to assess inflammatory status and immune disturbances in vivo and in vitro. We also outline findings of immune disturbances and signs of inflammation at the cellular, protein and brain imaging levels in patients with schizophrenia. Furthermore, we summarize the results from studies with anti-inflammatory or other immune-modulating drugs, highlighting how such studies have dealt with participant selection. Finally, we propose a strategy to construct an immune signature that may be helpful in selecting and monitoring participants in studies with immune modulating drugs and also applicable in regular clinical work.